PENGATURAN KEPEMILIKAN SERTIFIKASI KOMPETENSI BAGI TENAGA KERJA PROFESIONAL - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2020)
Professional workers who have competency certification at construction service companies are a must, bearing in mind that construction works are required to meet environmental and engineering management requirements in ensuring the orderly implementation of construction work. The problem in this research is how is the regulation regarding ownership of competency certification for professional workforce. This research uses a normative juridical approach and an empirical approach. The technique of data collection is done by literature study and field study. The data are then analyzed and discussed qualitatively. The results of this study indicate the Arrangement regarding ownership of competency certification for professional workers is contained in Article 70 of Law Number 2 of 2017 concerning Construction Services that every construction workforce working in the field of construction services is required to have a Work Competency Certificate. Technical arrangements are contained in the National Construction Services Development Agency Regulation No. 5 of 2017 concerning Certification and Registration of Experts which aims to realize an orderly implementation of certification and registration of Experts in accordance with the provisions stipulated by the LPJK. Suggestions in this study are companies engaged in construction services are advised to continue to improve competence to be more ready to compete.